2006
DOI: 10.1521/scpq.2006.21.3.286
|View full text |Cite
|
Sign up to set email alerts
|

Substance use as a robust correlate of school outcome measures for ethnically diverse adolescents of Asian/Pacific Islander ancestry.

Abstract: School psychologists are generally not provided with the knowledge and skills to address both educational and psychosocial issues of Asian American and Pacific Islander students. The present study is the first of its kind in examining 36 independent (i.e., demographic, social, cultural, psychological) variables in association with four school outcomes (i.e., grade point average, absences, suspensions, and school infractions) with a large sample of Caucasian, Filipino, Native Hawaiian, Japanese, mixed/non-Hawai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 93 publications
1
25
0
Order By: Relevance
“…Given the general finding of lower educational achievement being associated with poorer psychological adjustment (e.g., Hishinuma, Foster et al, 2001), and given the differential academic achievement among racial and ethnic groups (e.g., African Americans with lower high school GPAs than Caucasians; Caucasians with lower high school GPAs than Asian-Pacific Islanders), this area of study is critical in understanding the well-being of ethnic minorities. In the context of the present study, Native Hawaiian adolescents tend to have lower levels of achievement than non-Hawaiians in Hawai‘i (e.g., Hishinuma, Foster et al, 2001; Hishinuma, Johnson et al, 2001; Hishinuma et al, 2006). …”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations
“…Given the general finding of lower educational achievement being associated with poorer psychological adjustment (e.g., Hishinuma, Foster et al, 2001), and given the differential academic achievement among racial and ethnic groups (e.g., African Americans with lower high school GPAs than Caucasians; Caucasians with lower high school GPAs than Asian-Pacific Islanders), this area of study is critical in understanding the well-being of ethnic minorities. In the context of the present study, Native Hawaiian adolescents tend to have lower levels of achievement than non-Hawaiians in Hawai‘i (e.g., Hishinuma, Foster et al, 2001; Hishinuma, Johnson et al, 2001; Hishinuma et al, 2006). …”
Section: Introductionmentioning
confidence: 57%
“…This measurement of academic achievement demonstrated high concurrent validity with actual cumulative GPA in a sub-study of the same persons ( r =.76; Hishinuma, Johnson et al, 2001) and construct validity with adjustment indicators, arrests/serious trouble with the law, and substance use (Hishinuma, Foster et al, 2001; Hishinuma et al, 2006). …”
Section: Methodsmentioning
confidence: 85%
See 2 more Smart Citations
“…For example, it has been related to unsafe sexual practices (Ramisetty-Mikler et al, 2004), suicidal behavior (Else, Andrade, & Nahulu, 2007; Yuen, Nahulu, Hishinuma, & Miyamoto, 2000), poorer academic achievement (Hishinuma et al, 2006), and increases in school absences, suspensions, and infractions (Hishinuma et al, 2006) with this youth population. Further, compared with other ethnic groups, Wong et al (2004) found that Hawaiian youth reported the highest need for drug and alcohol treatment, particularly treatment related to alcohol and marijuana use.…”
Section: Drug Use Epidemiology Of Native Hawaiian Youthmentioning
confidence: 99%